Mental distress, addiction and suicide in the general population during the COVID-19 pandemic: A narrative review - Giuseppe FERRARI; Giorgia MARTORI (GIornale Italiano di Psicologia e Medicina del Lavoro)
Social distancing, isolation, quarantine, fear of contagion and the economic consequences of the COVID-19 pandemic have caused great harm to society and caused serious psychological trauma to many people. Emerging evidence suggests that the Coronavirus (COVID-19) pandemic may be negatively impacting mental health, leading to increased levels of anxiety, depression, stress, fear, sleep disorders, and symptoms of post-traumatic stress disorder. Aim of this paper was to review some mental health outcomes, namely internet dependance, eating disorders, alcohol and sub- stance disorders, and suicide risk in the public. A narrative review was carried out. Peer reviewed articles in English and Italian were searched on Pubmed and Google Scholar with the following key terms- “COVID-19”, “SARS-CoV2”, “Pandemic”, “Addiction”, “Opioid”, “Alcohol”, “Eating disorder”, “Addiction Psychiatry”, “Deaddiction”, “Domestic violence”, “Substance use disorders”, “Suicide”, “Internet dependance”, “Social Media”, “Behavioral addiction”. Few newspaper reports have also been added as per context. Our review showed an increased level of additive behaviours during this period. During quarantine, home risks become a very dangerous place for victims of domestic violence, thus increasing the psychological harm due to pandemic. Some categories like elderly persons, children and adolescents, health professionals, COVID-19 survivors, and people already affected by psychological disorders are at higher risk of suicide. During the COVID-19 pandemic and in the next future, policymakers should timely organize mental health services to tackle these issues.